Temperature detection and control in multiple DC motors. (2021) - Gowthaman, K.S.; Palaniyappan, S.; Hubert Tony Raj, L.; Sankara Subramanian, A.T.
Abstract: The industries in developing countries usually face the difficulty of the manual operations which will result in both accuracy and poor efficiency. This paper highlights the automation of a process Industry and at the same time monitoring operations are also done. In case of switching off of the single motor where the other motor runs at a specific load without any distraction can be done by using single circuitry of DC supply. The microcontroller and relays are being used for switching ONof all the DC motor. The main operation in this project is to sense the temperature of the DC motors which is done by temperature sensor. The scrutinized value of the DC motor's temperature are being displayed in the LCD.